ScVEGF-PEG-HBED-CC and scVEGF-PEG-NOTA conjugates: comparison of easy-to-label recombinant proteins for [68Ga]PET imaging of VEGF receptors in angiogenic vasculature - Eder, Matthias; Krivoshein, Arcadius V.; Backer, Marina; Backer, Joseph M.; Haberkorn, Uwe; Eisenhut, Michael (Nuclear medicine and biology, 2010)
Introduction - VEGF receptors play a key role in angiogenesis and are important targets for several approved and many experimental drugs. Imaging of VEGF receptor expression in malignant tumors would provide important information, which can influence patient management. The aim of this study was the development of an easy-to-label positron-emitting tracer for imaging VEGF receptors. The tracer is based on engineered single-chain VEGF (scVEGF), expressed with cysteine-containing fusion tag (Cys-tag) for site-specific conjugation of PEGylated bifunctional chelating agents, HBED-CC or NOTA, suitable for labeling with 68Ga at ambient temperature. - Methods - scVEGF-PEG-HBED-CC was synthesized by activating a single carboxyl group of the [Fe(HBED-CC)]- complex with N-hydroxysuccinimide. Reaction of the activated complex with NH2-PEG-maleimide was followed by site-specific conjugation of PEGylated chelator to a thiol group in Cys-tag of scVEGF. The scVEGF-PEG-NOTA conjugate was synthesized using NHS-PEG-maleimide and p-NH2-Bn-NOTA. 68Ga complexation was performed in HEPES buffer (pH 4.2) at room temperature. The functional activity after labeling was tested by radioligand cell binding assays. Biodistribution and PET studies in tumor-bearing mice were performed after 1, 2, 3 and 4 h postinjection. - Results - The radiolabeling of scVEGF-PEG-HBED-CC proved more efficient than scVEGF-PEG-NOTA allowing to stop the reaction after 4 min (>97% radiochemical yield). Radioligand cell binding assays performed on HEK-293 cells overexpressing VEGFR-2 revealed no change in the binding properties of 68Ga-radiolabeled scVEGF relative to other scVEGF-based tracers. Both tracers showed comparable results in biodistribution, such as tumor accumulation and low liver uptake. The tracers were stable in 50% human serum for at least 72 h. - Conclusions - The conjugates scVEGF-PEG-HBED-CC and scVEGF-PEG-NOTA revealed comparable in vivo characteristics and allowed easy-to-perform labeling with high stability for fast [68Ga]PET imaging of VEGF receptors in angiogenic vasculature.